An Analysis of the Process and Attributes Used in the Transaction Evidence Appraisal Method for USDA Forest Service Timber Sales in the US Southwest - Charles Tucker Herbert; Han-Sup Han; Mathew Smidt; Jaechoul Lee; Carlos Diniz (Journal of Forestry, 2026)

White ginseng ethanol extract inhibits melanogenesis in B16F10 cells by regulating the microphthalmia-associated transcription factor/tyrosinase pathway - Min Jung Kim; Ye Jin Yang; Ji Woong Heo; Han Nim Choi; Chae Un Lim; Se Hyo Jeong; Hun Hwan Kim; Gon Sup Kim; Young Hun Kim; Ju-Hye Yang; Kwang Il Park (Molecular & Cellular Toxicology, 2026)

Deactivation of Colletotrichum acutatum and Colletotrichum gloeosporioides by novel cylindrical dielectric barrier discharge plasma: Maintaining biochemical composition in strawberry by in-vitro and in-vivo - Sekar Ashokkumar; Roshani Dahal; Yung Oh Shin; Han Sup Uhm; Jang Sick Park; Young-Chul Lee; Eun Ha Choi (Food Control, 2026)

Comparative assessment of biochar reactor technologies for biomass conversion: Design, performance, and application suitability - Dipita Ghosh; Nathaniel Anderson; Han-Sup Han (Journal of Cleaner Production, 2026)

Composite of water-insoluble bentonite and liposomes for controlled intestinal release and enhanced oral bioavailability - Pil-Jae Song; Ho-Sup Jung; Yong-Hae Han; Min-Jun Baek; Dae-Duk Kim (Journal of Pharmaceutical Investigation, 2025)

6-PPD induces mitochondrial dysfunction and reduces healthspan and lifespan through SKN-1 in Caenorhabditis elegans - Moonjung Hyun; Laxmi Rathor; Hye-Jin Kim; Ho-Jeong Lee; Taylor McElroy; Moongi Ji; Min-Seok Choi; Steven Beck; Julia Bailey; Hun Hwan Kim; Yi Sheng; Jeong-Doo Heo; et al. (Journal of Hazardous Materials, 2025)

Disinfection of human coronavirus-229E on hospital cotton fabric via multi-cylinder dielectric barrier discharge plasma-generated reactive nitrogen species - Sekar Ashokkumar; Jun Sup Lim; Jinsung Choi; Shaik Abdul Munnaf; Ihn Han; Neha Kaushik; Nagendra Kumar Kaushik; Yung Oh Shin; Eun Ha Choi (Chemical Engineering Journal, 2025)

Multifunctionality of Vesicle-Associated Membrane Protein 721 and 722 in Plants - Hye Sup Yun; Ga E Kang; Goeun Han; Ki Nyeong Lee; Chian Kwon (Journal of Plant Biology, 2025)

Production and application of Paenibacillus polymyxa levan as an antiviral priming agent against cucumber mosaic virus infection in tobacco plants - Hyunjun Ko; Hangil Kim; Ji Won Heo; Sangjun Lee; Yongtae Yu; Hyebin Kim; Hyeon-Seok Oh; Chan-Gi Min; Seokmin Baek; Han Suk Choi; Sung Jin Moon; Woohyun Sim; et al. (Carbohydrate Polymers, 2025)

FireBox and CharBoss: An alternative to open burning of woody biomass - Paul O. Oyier; Han-Sup Han; Dipita Ghosh; Nathaniel Anderson; Deborah S. Page-Dumroese; Daniel W. McCollum; Joanne M. Tirocke; Derek N. Pierson (Biomass and Bioenergy, 2024)

Effect of Lactobacillus Rhamnosus GG for Regulation of Inflammatory Response in Radiation-Induced Enteritis - Sung Uk Lee; Bum-Sup Jang; Yi Rang Na; Sun Hwa Lee; Sunwoo Han; Ji Hyun Chang; Hak Jae Kim (Probiotics and Antimicrobial Proteins, 2024)

Development of polymorphic simple sequence repeat markers in Agastache rugosa and their application in genetic evaluation and cross-taxon transferability of Agastache species - Hye Ran Shin; Ick Hyun Jo; Raveendar Sebastin; Jinsu Gil; Gi Yeong Kim; Suyun Moon; Hyun-Seung Park; Sewon Oh; Jong Won Han; Kyung Ho Ma; Yi Lee; Daeil Kim; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

One-step wet-spinning of conducting polymer and cellulose nanofiber composites for fiber-type organic electrochemical transistors - Minhu Huang; Seunghyeon Lee; Il-Young Jo; Hyunbeen Park; Bong Sup Shim; Myung-Han Yoon (Carbohydrate Polymers, 2024)

The Cost of Forest Thinning Operations in the Western United States: A Systematic Literature Review and New Thinning Cost Model - Heesol Chang; Han-Sup Han; Nathaniel Anderson; Yeon-Su Kim; Sang-Kyun Han (Journal of Forestry, 2023)
Mechanical forest thinning treatments are implemented across the western United States (US) to improve forest health and reduce hazardous fuels. However, the main challenge in thinning operations is low financial feasibility. This study synthesized the stump-to-truck cost of forest thinning operations in the western US based on operations research articles published over the last 40 years (1980–2020). We systematically selected and reviewed 20 thinning studies to analyze key variables affecting machine productivity and harvesting costs. The average cost of forest thinning was lowest for a mechanized whole-tree thinning operation at $21.34/ton or $2,075/ha. Feller-bunchers and skidders showed the highest productivity in felling and extraction machines, respectively. We found that extraction cost accounted for the largest proportion of the stump-to-truck cost of forest thinning (33%, 43%, and 34% in whole-tree, tree-length, and cut-to-length thinning, respectively). Tree diameter and machine travel distance are common variables affecting thinning productivity and thus cost, regardless of the harvesting methods used. With thinning productivity and cost data from the selected studies, we developed a spreadsheet-based model to estimate thinning costs for various harvesting systems. This literature synthesis and new thinning cost model can help foresters develop a cost-effective plan for thinning operations.

Bed configurations in CO vacuum pressure swing adsorption process for basic oxygen furnace gas utilization: Experiment, simulation, and techno-economic analysis - Hyunmin Oh; Hee Tae Beum; Suh-Young Lee; Jinsu Kim; Jungil Kim; Yongju Yun; Sang Sup Han (Chemical Engineering Journal, 2023)

Protective effect of 7-hydroxyl-1-methylindole-3-acetonitrile on the intestinal mucosal damage response to inflammation in mice with DSS-induced colitis - Kyung-Sook Chung; Sang-Eun Park; Jung-Hun Lee; Su-Yeon Kim; Hee-Soo Han; Yong Sup Lee; Seang-Hwan Jung; Eungyeong Jang; Sangmin Lee; Kyung-Tae Lee (Chemico-Biological Interactions, 2023)

Forest Contracting Businesses in the US Southwest: Current Profile and Workforce Training Needs - Damon Vaughan; Catrin Edgeley; Han-Sup Han (Journal of Forestry, 2022)
We surveyed forestry contractors in three sectors (logging, mastication, and trucking) across the states of Arizona, New Mexico, and Colorado. Our survey sought to gather current demographic and background information on contractors as well as establish how a forest operations training center might address their employee training needs. Most of the businesses surveyed were small, with owner ages tending to be high (over 50) but employee ages much lower (under 40). Finding skilled workers was identified as the greatest barrier to success by the respondents, underscoring the need for more training opportunities. The majority of respondents (86%) did not have access to any external training programs. Survey results indicated a high demand for training programs for forestry contractors in the Southwest, which could play a vital role for the region to achieve landscape-scale forest restoration goals.

Factors Affecting Operational Cost and Productivity of Ground-Based Timber Harvesting Machines: a Meta-analysis - Libin T. Louis; Anil Raj Kizha; Adam Daigneault; Han-Sup Han; Aaron Weiskittel (Current Forestry Reports, 2022)

A Critical Review of Comminution Technology and Operational Logistics of Wood Chips - Raffaele Spinelli; Lars Eliasson; Han-Sup Han (Current Forestry Reports, 2020)

Enzyme immobilization on porous chitosan hydrogel capsules formed by anionic surfactant gelation - Amos K. Dwamena; Seung Han Woo; Chang Sup Kim (Biotechnology Letters, 2020)

Sternoclavicular septic arthritis caused by Staphylococcus aureus : excellent results from medical treatment and limited surgery - Young-Rock Jang; Taeeun Kim; Min-Chul Kim; Heung Sup Sung; Mi-Na Kim; Min Jae Kim; Sung Han Kim; Sang-Oh Lee; Sang-Ho Choi; Jun Hee Woo; Yang Soo Kim; Yong Pil Chong (Infectious Diseases, 2019)

Moisture Content in Forest Residues: an Insight on Sampling Methods and Procedures - Anil Raj Kizha; Han-Sup Han (Current Forestry Reports, 2017)

Genome-wide analysis of gene expression to distinguish photoperiod-dependent and -independent flowering in Brassicaceae - Hayoung Song; Hankuil Yi; Changhee Do; Ching-Tack Han; Ill-Sup Nou; Yoonkang Hur (Genes & Genomics, 2017)

Genome-wide analysis of genes associated with bolting in heading type chinese cabbage - Xiangshu Dong; Hankuil Yi; Ching-Tack Han; Ill-Sup Nou; AM Swaraz; Yoonkang Hur (Euphytica, 2016)

GDSL esterase/lipase genes in Brassica rapa L.: genome-wide identification and expression analysis - Xiangshu Dong; Hankuil Yi; Ching-Tack Han; Ill-Sup Nou; Yoonkang Hur (Molecular Genetics and Genomics, 2016)

Overexpression of the glutamine synthetase gene modulates oxidative stress response in rice after exposure to cadmium stress - Hye Jung Lee; Sailila E. Abdula; Dae Won Jang; Sung-Han Park; Ung-Han Yoon; Yu Jin Jung; Kwon Kyoo Kang; Ill Sup Nou; Yong-Gu Cho (Plant Cell Reports, 2013)

Inhibitory effects of epi-sesamin on endothelial protein C receptor shedding in vitro and in vivo - Sae-Kwang Ku; Wonhwa Lee; Hayoung Yoo; Chang-Kyun Han; Jong-Sup Bae (Inflammation Research, 2013)

Genome-wide expression profiles of contrasting inbred lines of Chinese cabbage, Chiifu and Kenshin, under temperature stress - Jeongyeo Lee; Yong-Pyo Lim; Ching-Tack Han; Ill-Sup Nou; Yoonkang Hur (Genes & Genomics, 2013)

Insects perceive local sex ratio in the absence of tactile or visual sex-specific cues - Chang S. Han; Chang-Ku Kang; Hong-Sup Shin; Jeong-Hyun Lee; Mi-Rye Bae; Sang-Im Lee; Piotr G. Jablonski (Behavioral Ecology and Sociobiology, 2012)

Increased Expression of Alpha-Synuclein by SNCA Duplication is Associated with Resistance to Toxic Stimuli - Han-Joon Kim; Beom S. Jeon; Min-Yung Yoon; Sung-Sup Park; Kwang-Woo Lee (Journal of Molecular Neuroscience, 2012)

Molecular characterization of a lectin, BPL-4, from the marine green alga Bryopsis plumosa (Chlorophyta) - Jong-Won Han; Kang-Sup Yoon; Min-Gui Jung; Kyong-Hwa Chah; Gwang-Hoon Kim (Algae, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Purification and characterization of a lectin, BPL-3, from the marine green alga Bryopsis plumosa - Jong Won Han; Kang Sup Yoon; Tatyana A. Klochkova; Mi-Sook Hwang; Gwang Hoon Kim (Journal of Applied Phycology, 2011)

Oligometastases confined one organ from colorectal cancer treated by SBRT - Jin-Kyu Kang; Mi-Sook Kim; Jin Ho Kim; Seong Yul Yoo; Chul Koo Cho; Kwang Mo Yang; Hyung Jun Yoo; Young Seok Seo; Dong Han Lee; Hae Jin Kang; Young Han Kim; Ui-Sup Shin (Clinical & Experimental Metastasis, 2010)

Hypothyroidism Induced by Polychlorinated Biphenyls and Up-Regulation of Transthyretin - Dae-Yong Han; Sang-Rim Kang; Oh-Sung Park; Jae-Hyeon Cho; Chung-Kil Won; Hyeon-Soo Park; Kwang-Il Park; Eun-Hee Kim; Gon-Sup Kim (Bulletin of Environmental Contamination and Toxicology, 2010)

Low contribution of BRCA1/2 genomic rearrangement to high-risk breast cancer in the Korean population - Moon-Woo Seong; Sung Im Cho; Dong-Young Noh; Wonshik Han; Sung-Won Kim; Chul-Min Park; Hyun-Woong Park; So Yeon Kim; Ji Yeon Kim; Sung Sup Park (Familial Cancer, 2009)

Introducing pulsed low-intensity ultrasound to culturing human umbilical cord-derived mesenchymal stem cells - Jong Hyun Yoon; Eun Youn Roh; Sue Shin; Nam Hee Jung; Eun Young Song; Dong Soon Lee; Kyou Sup Han; Joung Sung Kim; Byoung Jae Kim; Hye Won Jeon; Kang Sup Yoon (Biotechnology Letters, 2009)

Fetal mesenchymal stem cells derived from human umbilical cord sustain primitive characteristics during extensive expansion - Chris H. Jo; Ok-Su Kim; Eun-Young Park; Byoung Jae Kim; Ji-Ho Lee; Seung-Baik Kang; Jae Hyup Lee; Hyuk Soo Han; Seung Hwan Rhee; Kang-Sup Yoon (Cell and Tissue Research, 2008)

Physiological and chemical characteristics of field-and mountain-cultivated ginseng roots - Yong Eui Choi; Yong Suk Kim; Myong Jong Yi; Wan Geun Park; Jae Seon Yi; Seong Ryeol Chun; Sang Sup Han; Sung Jae Lee (Journal of Plant Biology, 2007)

Transgenic watermelon rootstock resistant to CGMMV (cucumber green mottle mosaic virus) infection - Sang Mi Park; Jung Suk Lee; Sung Jegal; Bo Young Jeon; Min Jung; Yoon Sik Park; Sang Lyul Han; Yoon Sup Shin; Nam Han Her; Jang Ha Lee; Mi Yeon Lee; Ki Hyun Ryu; et al. (Plant Cell Reports, 2005)

Origin of Mesozoic gold mineralization in South Korea - Seon‐Gyu Choi; Sung‐Tack Kwon; Jin‐Han Ree; Chil‐Sup So; Sang Joon Pak (Island Arc, 2005)
The Mesozoic gold–silver deposits in South Korea are closely associated with the Mesozoic granitoids. The Jurassic gold–silver deposits can be distinguished from the Cretaceous ones in terms of occurrence, alteration style, gold fineness, associated mineral assemblage, fluid inclusion and stable isotopic compositions. The Jurassic deposits were formed in mesozonal environments related to deep‐seated granitoids, whereas the Cretaceous ones were formed in epizonal environments related to shallow‐level granitoids. The Jurassic auriferous deposits (about 165–145 Ma) show fluid characteristics typical of an orogenic‐type gold deposit, and were probably generated in a compressional regime caused by an orthogonal convergence of the Izanagi oceanic plate into the Asiatic margin. However, strike‐slip faults and caldera‐related fractures, together with subvolcanic to volcanic activity, may have played an important role in the formation of Cretaceous gold–silver lode deposits (about 110–45 Ma) under a continental arc setting.